Cognitive grammar and aphasic discourse. (2nd June 2016) - Manning, Molly; Franklin, Sue
ABSTRACT: In cognitive grammar (CG), there is no clear division between language and other cognitive processes; all linguistic form is conceptually meaningful. In this pilot study, a CG approach was applied to investigate whether people with aphasia (PWA) have cognitive linguistic difficulty not predicted from traditional, componential models of aphasia. Narrative samples from 22 PWA (6 fluent, 16 non-fluent) were compared with samples from 10 participants without aphasia. Between-group differences were tested statistically. PWA had significant difficulty with temporal sequencing, suggesting problems that are not uniquely linguistic. For some, these problems were doubly dissociated with naming, used as a general measure of severity, which indicates that cognitive linguistic difficulties are not linked with more widespread brain damage. Further investigation may lead to a richer account of aphasia in line with contemporary linguistics and cognitive science approaches.